AN ANALYSIS ON CUSTOMERS’ LEVEL OF EXPERIENCE TOWARD SATISFACTION, IMAGE AND LOYALTY IN PEOPLE BASED SERVICE INDUSTRY, IN PARTICULAR SALON INDUSTRY IN JAKARTA - Lydia M. Iswara; Stephanie Astri Suryani (Journal of Business Strategy and Execution, 2010)
The research was conducted to analyze the effect of customers' level of experience towards their satisfaction, image and loyalty in hair salon industry in Jakarta, which was adapted from the research done by Brunner, Stocklin, & Opwis in 2008. Data collection method used in gathering 300 questionnaires was email, social networks approach and store intercept interview. The data gathered were then analyzed using Descriptive Analysis, Correlation Bivariate, ANOVA, T-test, Mean Value Analysis, and Multiple Regressions. The result indicates that there was positive relationship between satisfaction, image and loyalty. The role of experience was also proven exist although its existence was resulting in a different way from the previous study. In this study, total satisfaction was verified as the general indication for loyalty, while role of experience existed where new customer paid more attention for transaction specific satisfaction and experienced customer put more consideration on cumulative satisfaction. New customers were proven to have different views towards satisfaction, image and loyalty compared to experienced customers. Therefore, hair salons need to differentiate their strategies between new and experienced customers.